Qi, Return to Bodily Experience: A New Perspective of Qi and Qigong Experience Research - Xinzhe Huang (Chinese Medicine and Culture)
For a long period, Qi and Qigong experience were studied within the theoretical framework of natural science, psychology, and TCM. This article reviews the modes and problems of Qi and Qigong researches, discusses the theoretical basis of phenomenological researches in anthropology, exemplifies some important researches and ideas about bodily experience. Furthermore, the possibility and difficulty of utilizing these methodologies and ideas are analyzed out as well. Aims to open up a brand-new horizon of Qi and Qigong research, enriches our understandings of the culture of Qi and Qigong, and makes Qigong better adapt itself to the contemporary and the world.